The Influence Of Motivation And Work Discipline On Employee Performance At PT. Pertama Logistics Service Tanjung Priok Branch - Pricilla, Lidya (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of motivation and work discipline on employee performance at PT. Pertama Logistics Service, Tanjung Priok Branch. The research method used is quantitative with an associative approach. Data was collected through questionnaires distributed to 80 respondents and analyzed using multiple linear regression analysis with the assistance of SPSS version 25. The research findings indicate that motivation and work discipline simultaneously have a significant effect on employee performance. Partially, work discipline has a more dominant influence than motivation, suggesting that adherence to regulations plays a greater role in improving performance. Additionally, absenteeism and tardiness remain factors affecting productivity. This study concludes that implementing policies that balance motivation and work discipline can optimize employee performance.